Effects of bovine subclinical mastitis caused by Corynebacterium spp. on somatic cell count, milk yield and composition by comparing contralateral quarters - Gonçalves, Juliano Leonel; Tomazi, Tiago; Barreiro, Juliana Regina; Beuron, Daniele Cristine; Arcari, Marcos André; Lee, Sarah Hwa In; Martins, Cristian Marlon de Magalhães Rodrigues; Araújo Junior, João Pessoa [UNESP]; Santos, Marcos Veiga dos (Elsevier, 2016)
Subclinical mastitis caused by Corynebacterium spp. (as a group and at the species level) was investigated by evaluating contralateral (healthy and infected) mammary quarters for somatic cell count (SCC), milk yield and composition. Selection of cows with subclinical mastitis caused by Corynebacterium spp. was performed by microbiological culture of composite samples collected from 1242 dairy cows from 21 dairy herds. For each of the selected cows, milk yield was measured and milk samples were collected at the mammary quarter level (i.e., 1140 mammary samples collected from 285 cows) for analysis of milk composition and SCC. The identification of Corynebacterium spp. isolates was performed by 16S rRNA gene sequencing. One hundred and eighty Corynebacterium spp. isolates were identified, of which 167 (92.77%) were C. bovis and eight (4.44%) non-C. bovis; for five of the Corynebacterium spp. isolates (2.77%), sequencing of 16S rRNA genes did not allow identification at the species level. Mammary quarters infected with Corynebacterium spp. as a group had a higher geometric mean SCC (197,900 cells/mL) than healthy contralateral mammary quarters (85,800 cells/mL). Species of Corynebacterium non-C. bovis were infrequently isolated and did not change SCC, milk yield or milk solid contents when evaluated at the contralateral quarter level. Although C. bovis infection showed no effect on milk yield, fat, protein, casein or total solids in milk, it increased SCC and decreased lactose and milk solids non-fat content.
Keywords: Corynebacterium spp; Milk composition; Milk yield; Minor pathogens; Somatic cell count; Subclinical mastitis